An Evaluation Of The Enjoyment Levels Of Participants Of LifeLab, A Health Literacy Intervention For Socially Disadvantaged Adolescents. - Lorna Burke; Dr. Hannah Goss; Craig Smith; Dr. Johann Issartel; Dr. Sarahjane Belton (SURE Journal: (Science Undergraduate Research Experience Journal))
Aim: LifeLab is co-designed by and for Junior Cycle students from social disadvantage in Ireland, with the hope to improve health literacy and subsequent health outcomes in this cohort. The aim of this study was to evaluate the enjoyment levels of students participating in the pilot of LifeLab, with a view to informing future development of the intervention. Method: As part of the process evaluation of the pilot of LifeLab, a series of focus groups and purposively designed enjoyment scales were completed by 80 adolescents, from one disadvantaged school in Dublin, Ireland. Inductive thematic analysis was carried out to analyse focus group data, and descriptive analysis of the enjoyment scales was conducted. Findings of the focus groups and enjoyment scales were synthesised and integrated resulting in the generation of a series of higher order and lower order themes of enjoyment. Results: Results of the inductive thematic analysis identified barriers, facilitators and suggestions for increasing enjoyment. Adolescents' enjoyment of the LifeLab intervention can be improved through the integration of fun activity-based learning, competition, variety, and challenge. Conclusions: Findings suggested specific areas of improvement within the intervention, and by using the participant voice, these factors can be incorporated within the LifeLab intervention. It is hoped these refinements, as part of ongoing intervention development, may increase levels of enjoyment, which will therefore enhance the usability and success of LifeLab.